Exploring the interplay of mindfulness, self-efficacy, and burnout among Chinese preschool teachers: a network approach - Yan, Lingyan; Lin, Yunxiang; Li, Wenjie; Hu, Changsheng (Frontiers in Psychology, 2025)
BackgroundTeacher burnout is associated with a series of negative outcomes for teachers and children. Previous studies have confirmed the impact of teaching mindfulness and teacher self-efficacy on teacher burnout, but the relationship between them needs further research.MethodsThis study was conducted in May 2024 on 572 kindergarten teachers in Sichuan and Yunnan provinces using the Mindfulness in Teaching Scale, the Teacher Sense of Self-Efficacy Scale, the Teacher Burnout Scale, and SPSS software for descriptive statistical analysis, and R software for network analysis.ResultsThe teacher mindfulness–teacher burnout network had 20 cross-community edges, the strongest of which were M1, “Non-automated instruction;” J2, “Depersonalization;” and M7, “Appropriate expression of pain,” which is demonstrated by these values displaying the highest bridge expected influences. The teacher self-efficacy-teacher burnout network had 16 cross-community edges, the strongest of which were S2, “Encouraging young children to love learning;” J3, “Low achievement;” and S11, “Home-school cooperation to help young children,” demonstrated by these values displaying the highest bridge expected influences.ConclusionThis study explored the relationships between teaching mindfulness, teacher self-efficacy, and teacher burnout using network analysis methods. The teaching mindfulness factor M7, “Appropriate expression of pain,” and the teacher self-efficacy factor S11, “Home-school cooperation to help young children,” showed negative correlations with various burnout factors. These factors were identified as the highest bridge centrality nodes, suggesting a stronger association with teacher burnout than other factors. Thus, they represent the optimal targets for interventions aimed at reducing teacher burnout.